Genetics of Lipodystrophy: Can It Help in Understanding the Pathophysiology of Metabolic Syndrome? - Mathur, Sandeep Kumar (Biomolecules, 2018)
Understanding phenotypes and their genetic determinants for metabolic syndrome (MetS) has been quite challenging. With the advent of systems genomic approaches, there is a need to decipher methods for identification and evaluating the functional role of phenotypic traits associated with complex diseases, such as MetS. The monogenic syndromes of lipodystrophy are well understood, but the molecular pathophysiology of insulin resistance (IR) underpinning the obesity, diabetes mellitus, and dyslipidemia is not well deciphered. In this commentary, we argue the role of pathophysiology of MetS, and its effects into possible understanding of genetic determinants associated with lipodystrophy-mediated diabetes mellitus.